Cellular and Molecular Mechanisms of REM Sleep Homeostatic Drive: A Plausible Component for Behavioral Plasticity - Datta, Subimal; Oliver, Michael D. (Frontiers in Neural Circuits, 2017)
Homeostatic regulation of REM sleep drive, as measured by an increase in the number of REM sleep transitions, plays a key role in neuronal and behavioral plasticity (i.e. learning and memory). Deficits in REM sleep homeostatic drive (RSHD) are implicated in the development of many neuropsychiatric disorders. Yet, the cellular and molecular mechanisms underlying this RSHD remain to be incomplete. To further our understanding of this mechanism, the current study was performed on freely moving rats to test a hypothesis that a positive interaction between extracellular-signal-regulated kinase 1 and 2 (ERK1/2) activity and BDNF signaling in the PPT is a causal factor for the development of RSHD. Behavioral results of this study demonstrated that a short period (< 90 min) of selective REM sleep restriction (RSR) exhibited a strong RSHD. Molecular analyses revealed that this increased RSHD increased phosphorylation and activation of ERK1/2 and BDNF expression in the PPT. Additionally, pharmacological results demonstrated that the application of the ERK1/2 activation inhibitor U0126 into the PPT prevented RSHD and suppressed BDNF expression in the PPT. These results, for the first time, suggest that the positive interaction between ERK1/2 and BDNF in the PPT is a casual factor for the development of RSHD. These findings provide a novel direction in understanding how RSHD-associated specific molecular changes can facilitate neuronal plasticity and memory processing.